Simultaneous 8.2 keV phase-contrast imaging and 24.6 keV X-ray diffraction from shock-compressed matter at the LCLS - Seiboth, F; Fletcher, L; McGonegle, D; Anzellini, S; Dresselhaus-Cooper, L; Frost, M; Galtier, E; Goede, S; Harmand, M; Lee, H; Levitan, A; Miyanishi, K; et al. (AIP Publishing, 2018)
In this work, we demonstrate simultaneous phase-contrast imaging (PCI) and X-ray diffraction from shock compressed matter at the Matter in Extreme Conditions (MEC) endstation, Linac Coherent Light Source (LCLS). We utilize the chromaticity from compound refractive X-ray lenses to focus the 24.6 keV 3rd order undulator harmonic of the LCLS to a spot size of 5 μm on target to perform X-ray diffraction. Simultaneous PCI from the 8.2 keV fundamental X-ray beam is used to visualize and measure the transient properties of the shock wave over a 500 μm field of view. Furthermore, we demonstrate the ability to extend the reciprocal space by 5˚A−1, relative to the fundamental X-ray energy, by utilizing X-ray diffraction from the 3rd harmonic of the LCLS.